2010
DOI: 10.1089/scd.2009.0076
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Co-Signaling Molecule B7-H4 Is Expressed by Human Bone Marrow–Derived Mesenchymal Stem Cells and Mediates its T-Cell Modulatory Activity

Abstract: Though experimental evidence shows that human bone marrow-derived mesenchymal stem cells (hBMSCs) are able to suppress T-cell activation and proliferation, the precise mechanisms are still not completely understood. Here, we investigated the role of the negative costimulatory molecule B7-H4 in the immunosuppressive effect of hBMSCs on T-cell activation. We showed that B7-H4 expresses abundantly on hBMSCs assessed by reverse transcription, immunofluorescence staining, and flow cytometric analysis. Further studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Important mediators secreted by MSCs are prostaglandin E2 (PGE2) [13,14], indolamine 2,3-dioxygenase enzyme [15,16], nitric oxide [17,18], transforming growth factor-beta, and hepatocyte growth factor [8,19]. In addition, MSCs have been shown to express the coinhibitory molecules B7-H1 and B7-H4 [20,21], the notch ligand Jagged-1 [22], and galectin-1 [23] on their surface, which negatively interfere with immune responses. Furthermore, maximum anti-inflammatory and immunosuppressive effects can be evoked if MSCs are activated in a proinflammatory microenvironment by the presence of cytokines such as interferon-gamma, tumor necrosis factor-alpha (TNF-a), and/or interleukin-1-beta (IL-1b) [24,25].…”
Section: Au3 Cmentioning
confidence: 99%
“…Important mediators secreted by MSCs are prostaglandin E2 (PGE2) [13,14], indolamine 2,3-dioxygenase enzyme [15,16], nitric oxide [17,18], transforming growth factor-beta, and hepatocyte growth factor [8,19]. In addition, MSCs have been shown to express the coinhibitory molecules B7-H1 and B7-H4 [20,21], the notch ligand Jagged-1 [22], and galectin-1 [23] on their surface, which negatively interfere with immune responses. Furthermore, maximum anti-inflammatory and immunosuppressive effects can be evoked if MSCs are activated in a proinflammatory microenvironment by the presence of cytokines such as interferon-gamma, tumor necrosis factor-alpha (TNF-a), and/or interleukin-1-beta (IL-1b) [24,25].…”
Section: Au3 Cmentioning
confidence: 99%
“…In vitro data from our group recently demonstrated that WJ-MSC do express relevant immunomodulatory molecules both in their naïve and differentiated state, as demonstrated for osteogenic, adipogenic and hepatogenic differentiation protocols [56,57].…”
Section: Immunomodulation and Differentiation: Can We Get Them Togethmentioning
confidence: 99%
“…Both soluble mediators and modulation exerted via complex networks of cytokines and costimulatory molecules appear to play a role in MSC regulation of T cells, and these mechanisms invoke both contact-dependent and -independent pathways. Although many of the studies use MSC-conditioned medium, both contact-dependent andindependent mechanisms are probably invoked in the therapeutic use of MSCs (20,71). In addition to cytokines, the network of costimulatory molecules is hypothesized to play a prominent role in modulating tolerance and inflammation.…”
Section: Immunomodulatory Effect Of Mesenchymal Stem Cells In Adaptivmentioning
confidence: 99%
“…The B7 family members-inducible co-stimulator (ICOS) ligand, PD-L1 (B7-H1), PD-L2 (B7-DC), B7-H3, and B7-H4 (B7x/B7-S1)-are expressed on professional APC cells, while B7-H4 and B7-H1 are expressed on hMSCs and on cells within non-lymphoid organs. These observations may provide a new means for regulating T-cell activation and tolerance in peripheral tissues (31,71,78). ICOS and PD-1 are expressed upon T-cell-induction, and they regulate previously activated T-cells (79).…”
Section: Immunomodulatory Effect Of Mesenchymal Stem Cells In Adaptivmentioning
confidence: 99%